Randomized trial of albinterferon alfa-2b every 4 weeks for chronic hepatitis C virus genotype 2/3 - Pianko S. (2014)
Summary.  Albinterferon alfa-2b (albIFN) is a fusion protein of recombinant human albumin/recombinant interferon (IFN)-α-2b, with ∼200-h half-life. Safety/efficacy of albIFN q4wk was evaluated in 391 treatment-naive patients with chronic hepatitis C virus (HCV) genotype 2/3. Patients were randomized 3:4:4:4 to one of four open-label treatment groups: pegylated IFN (Peg-IFN)-α-2a 180 μg qwk or albIFN 900, 1200 or 1500 μg q4wk, plus oral ribavirin 800 mg/day, for 24 weeks. Primary efficacy endpoint was sustained virologic response (SVR; HCV RNA <20 IU/mL 24 weeks post-treatment). SVR rates were as follows: 85%, 76%, 76% and 78% with Peg-IFNα-2a and albIFN 900, 1200 and 1500 μg, respectively (P = NS); corresponding rapid virologic response rates (HCV RNA <43 IU/mL at week 4) were as follows: 78%, 49% (P < 0.001), 60% (P = 0.01) and 71%. SVR rates were not influenced by interleukin 28B genotype, although rapid virologic response rates were greater with interleukin 28B CC (P = NS). Serious adverse event rates were as follows: 4%, 11%, 3% and 3% with Peg-IFNα-2a and albIFN 900, 1200 and 1500 μg, respectively. No increase in serious/severe respiratory events was noted with albIFN. Fewer absolute neutrophil count reductions <750/mm(3) occurred with albIFN (P = 0.03), leading to fewer IFN dose reductions. Haemoglobin reductions <10 g/dL were less frequent with albIFN 900 and 1200 μg vs 1500 μg and Peg-IFNα-2a (P = 0.02), leading to fewer ribavirin dose reductions. albIFN administered q4wk produced fewer haematologic reductions than Peg-IFNα-2a, but had numerically lower SVR rates (P = NS) in patients with chronic HCV genotype 2/3.